A qualitative study exploring perceived barriers to infant feeding and caregiving among adolescent girls and young women in rural Bangladesh - Hackett, Kristy M. (BMC Public Health, 2015)
BACKGROUND: Infant feeding and caregiving by adolescent girls and young women in rural Bangladesh remains relatively understudied despite high potential vulnerability of younger mothers and their children due to poverty and high rates of early marriage and childbearing. This key knowledge gap may hamper the effectiveness of maternal, infant and child health interventions not specifically tailored to teenage mothers. This study aimed to narrow this gap by documenting key barriers to optimal infant and young child feeding and caregiving perceived by adolescent girls and young women in rural Bangladesh. METHODS: Focus group discussions and in-depth semi-structured interviews were conducted with 70 adolescent girls and young women participating in a community-based adolescent empowerment program in two rural regions of northwestern Bangladesh. Participants were stratified into three groups: unmarried, married without child, and married with child(ren). Thematic analysis was performed to elucidate dominant ideas regarding challenges with child feeding and caregiving across participant strata. RESULTS: Participants in all three strata and in both geographical regions attributed actual and anticipated caregiving difficulties to five major contextual factors: early marriage, maternal time allocation conflicts, rural life, short birth intervals, and poverty. Indications are that many girls and young women anticipate difficulties in feeding and caring for their future children from an early age, and often prior to motherhood. Participants articulated both perceived need and unmet demand for additional education in infant and young child feeding, childcare, and family planning techniques. CONCLUSIONS: Provision during adolescence of appropriate education, services and financial aid to support best practices for infant feeding and childcare could significantly improve maternal self-efficacy, mental health, nutrition security and young childcare, nutrition and health in rural Bangladesh. Lessons learned can be applied in future programs aimed at supporting adolescent women along a continuum of care.